Moral and Democratic Society System in Twain’s The Man Who Corrupted Hadleyburg - Ali, Muhammad Ilham; Tatipang, Devilito Prasetyo (Faculty of Humanities, Universitas Jenderal Soedirman, 2023)
This article sought to explore moral and democratic society systems within Mark Twain's short story